Effect of cooling system design on the performance of the recompression CO2 cycle for concentrated solar power application. (1st August 2019) - Ehsan, M. Monjurul; Duniam, Sam; Li, Jishun; Guan, Zhiqiang; Gurgenci, Hal; Klimenko, Alexander
Abstract: The thermal performance of a supercritical CO2 (sCO2 ) recompression cycle is expressively influenced by main compressor inlet temperature. Design of the cooling system is imperative since the compressor inlet temperature substantially influence the system performance. Due to nonlinear variation of both thermal and transport properties of the CO2 under critical condition, the cooling tower design and selection for the sCO2 cycle power plant is quite different from the power plants with steam cycle. The present work comprehensively investigates the effect of cooling system design on the optimal cycle performance under different operating condition. An iterative section method is applied while designing and optimizing the air-cooled heat exchanger bundles inside the tower. Prior to the design of natural draft dry cooling tower (NDDCT), an optimal operating condition is rectified at which the cycle efficiency is maximal. The tower performance is investigated by demonstrating unit height heat rejection and average heat rejection by each heat exchanger bundle. A detailed economic analysis of NDDCT is performed which takes account of capital cost, maintenance cost, annual cost, and specific investment cost. The thermo-economic assessment of the NDDCT is conducted by the influence of sCO2 inlet temperature inside the tower and variation of ambient air. Highlights: Detailed modelling of NDDCT coupled with the recompression sCO2 cycle. Implementation of iterative section method for sCO2 heat exchanger unit. Detailed economic analysis of NDDCT. Impact of variant sCO2 and air temperature on the system performance. Exergy and component-wise irreversibility analysis.